2019
DOI: 10.1080/17437199.2019.1641425
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors related to time to help-seeking for cancer symptoms: a meta-analysis across cancer sites

Abstract: The time patients wait before seeking help for cancer symptoms is among the most important factors contributing to diagnostic delays in cancer. We reviewed the association between time to help-seeking and three psychological factors: symptom knowledge, symptom interpretation, and beliefs about cancer (Prospero review protocol CRD42018088944). Forty-seven studies published between 1990 and 2019 met the inclusion criteria, providing data on 44,961 participants from 22 countries concerning seven cancer sites. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 79 publications
1
28
1
Order By: Relevance
“…Low-and middle-income (LMICs) countries were represented, however, studies in LMICs where conducted mainly with patient-rather than healthypopulations. Findings suggested that higher income (inequality) was related to stronger protective effects in relation to cancer symptom knowledge [17]. The weak relationship between respondents with higher vs lower symptom awareness in the findings presented here may be due, partly, to the small number of participants who reported anticipated delayed help-seeking for >2 weeks for breast and colorectal cancer symptoms.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Low-and middle-income (LMICs) countries were represented, however, studies in LMICs where conducted mainly with patient-rather than healthypopulations. Findings suggested that higher income (inequality) was related to stronger protective effects in relation to cancer symptom knowledge [17]. The weak relationship between respondents with higher vs lower symptom awareness in the findings presented here may be due, partly, to the small number of participants who reported anticipated delayed help-seeking for >2 weeks for breast and colorectal cancer symptoms.…”
Section: Discussioncontrasting
confidence: 50%
“…Findings from the ICBS also suggested that not recognising a symptom as a potential cancer sign was associated with an anticipated delay in help-seeking for all three symptoms; and a meta-analysis of studies from 22 different countries, which concluded that better symptom knowledge (OR=0.73, 95% CI 0.63, 0.84) and more positive beliefs about cancer (OR=0.70, 95% CI 0.52, 0.92) were associated with lower odds of a delay in help-seeking in healthy adult populations, universally [17]. Most studies were from the UK and other high-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Most research on cancer symptom appraisal and helpseeking has been conducted in HIC. In two previous systematic reviews of psychosocial influences on helpseeking for cancer symptoms, only 10% 14 and 15% 15 of studies were conducted in LMICs. Previous systematic reviews conducted in LMICs have focused on understanding barriers to help-seeking for breast or head and neck cancer using narrative data synthesis.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…In order for an event to occur, the patient must first seek medical care. The extent to which care is sought for symptoms varies not only by symptom knowledge, interpretation, and beliefs (Petrova et al, 2019), but also by ethnicity (Williams et al, 2019), socioeconomic status (McCutchan et al, 2015, and gender (Magaard et al, 2017). Second, the presence or absence of an event is subject to the clinical judgment of a provider.…”
Section: Stage 1 (Event Occurs)mentioning
confidence: 99%